Goldoni in the Translation of Amfiteatrov’s Family - Mikhail L. Andreev (Studia Litterarum)
Translations of Goldoni’s plays into Russian by A.V. and A.I. Amfiteatrov, a married couple who compiled Goldoni’s first collection in Russia, illustrate two basic approaches to translating fiction. In the plays that have not lost their repertoire potential, the translators depart from the original far enough, omitting dozens of phrases and whole replicas. The translation of The Comic Theater, a staged dramatic manifesto of Goldoni, pedantically follows the original, not only not allowing any omissions but also adhering to lexical and syntactical literalism. As a rule, free translation and accurate translation alternate as two models or templates in the history of translation. In the mentioned Goldoni’s collection, two alternative translations present themselves as two equal modes of transmitting a text into the foreign language which seems to be a rare, if not a unique phenomenon.